The Dual Model of Practical Professional and Pedagogical Training of Future Teachers for Vocational Schools in Germany - Turchyn, Andrii; Kashuba, Olexandra; Kravchuk Тetiana; Navolska, Halyna; Derkach, Halyna (Journal of Education Culture and Society, 2022)
Aim. The aim of the research is to identify and analyse the particularities of a dual model of practical professional and educational training of future vocational school teachers in Germany; to outline the prospects for the use of advanced ideas and positive experience of such a model in the training teachers in higher pedagogical educational institutions. Methods. The following methods have been used: interpretative - analytical method, some elements of general philosophical dialectical method (analysis, synthesis, analogy, comparing, systematisation, generalisation); empirical level methods (interview, observation); the method of theoretical generalisation. Results. The prospects of using the positive experience of a dual model of practical professional and pedagogical training of teachers of vocational school in Germany in a similar practice of teacher training have been determined: initiation of previous practical activity in the production of the chosen speciality as a necessary prerequisite for admission to a higher education institution; introduction of pedagogical internship; cooperation of higher education institutions with enterprises, institutions and organisations. Conclusion. A dual model of organising practical vocational training for future vocational school teachers, guarantees a high level of practical training for higher education applicants, makes balance among the educational needs of young people, labour market requirements and educational opportunities. Originality. The structure and content of the practical training of future professional school teachers in Germany have been characterised; the features of a dual model approach to its organisation have been investigated.